An assessment of facilities and activities under integrated child development services in a city of Darjeeling district, West Bengal, India - Saha, Mausumi; Biswas, Romy (International Journal Of Community Medicine And Public Health, 2017)
Background: ICDS is the unique community based programme for early childhood care and development. The objective of the study were to assess the facilities and activities of ICDS centres and the utilization of ICDS services among children aged 6 months to 6 years in a city of Darjeeling district, West Bengal, India. Study setting and design – Community based cross-sectional study done in a city of Darjeeling District of West Bengal, India during June – September 2016. Methods: 30 ICDS centres were selected by cluster sampling method. From each cluster 7 households were selected randomly with help of register of AWCs. 30 AWWs and 210 mothers of 6 months – 6 years children were interviewed with pre-designed, pre-tested schedule. Results: 86.66% AWCs were running in pukka building. Toilet facility was absent in 43.33% AWC. All AWCs were well equipped & all workers were literate. 65.12% male child and 70.74% female child had received supplementary nutrition. Immunization records were present in all AWC. NHED was celebrated in all AWC twice monthly. 80% AWC referred sick children verbally. 17.61% of children took the meal to their home and 29.57% mother didn’t attend NHED meeting. Conclusions: There was gap in infrastructural facility and some activities. Mothers were satisfied with overall functioning of AWC.